The Availability Of Social Responsibility In Protecting The Consumer From The Point Of View Of Consumers Of Household Electrical Appliances In The Syrian Coast - سليمان نبيلة; رشيد مصطفى أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to determine the extent of social responsibility in protecting the consumer in the household electrical appliances companies in Syria, and the researcher relied on the descriptive analytical approach in achieving the research goals, and a questionnaire was designed based on previous studies distributed to 383 individuals from the consumer of electrical household appliances in the coast Syrian, to study the vocabulary of research, inventory and collect the field information necessary for the subject of the research, and then it was emptied and analyzed using the SPSS statistical program, and has reached the following most important results: There is still ambiguity and insufficient knowledge on the part of the consumer with the concept of responsibility Social companies, their dimensions and the extent of their development, as well as the extent of its effectiveness and how to develop it and benefit from it, and that the original household electrical appliances companies enjoy economic responsibility and legal responsibility, and moral responsibility, but do not have charitable responsibility from the point of view of the members of the sample, and that charitable responsibility is less available in the original companies by 51.68%, followed by legal responsibility, and then moral responsibility, while economic responsibility is more available in consumer protection from the point of view of the respondents in the Syrian coast at 75.87%.